Complete mitochondrial genome sequence of the Indian pipistrelle Pipistrellus coromandra (Vespertilioninae) - Rahman, Md. Mafizur; Yoon, Kwang Bae; Kim, Ji Young; Hussin, Mohamed Zakaria; Park, Yung Chul (Taylor & Francis, 2016)
We characterized the complete mitogenome of Pipistrellus coromandra (Indian pipistrelle) for comparative analysis of mitogenomes and for resolving the phylogenetic relationship of four tribes in the subfamily Vespertilioninae. The mitogenome size of P. coromandra was 17,153 bp, with a control region and a typical set of 37 mitochondrial genes. The nucleotide composition of the P. coromandra mitogenome showed an AT bias with a nucleotide composition of 33.5% A, 30.7% T, 13.3% G, and 22.5% C. The mitochondrial protein-coding genes in P. coromandra use the standard start codon (ATN), two stop codons (TAA and AGA), and two incomplete stop codons (TA- and T--). The intertribal relationship of four tribes was highly resolved from the phylogenetic analysis of mitogenome sequences.